ANALISIS FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI DALAM PERSFEKTIF FRAUD HEXAGON - i gusti ayu novitasari, novitasari; Bagus Made Utama, Ida (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2024)
Fraudulent financial reporting (FFR) is a fraudulent practice carried out by company management in presenting misleading financial information. FFR practices can harm various stakeholders, such as investors, regulators, and the overall capital market. The aim of this study is to analyze the influence of stimulus, Opportunity, rationalization, Capability, ego, and collusion on the level of risk of fraudulent financial reporting in mining sector on the IDX. The research employs a quantitative method with a population mining sector listed on the IDX during the period 2019-2023. A sample of 110 companies was selected using purposive sampling technique. Data were collected through the analysis of financial statements published on the companies' websites or the IDX website. Data analysis was conducted using logistic regression to identify the relationship between independent variables (stimulus, Opportunity, rationalization, Capability, ego, collusion) and the dependent variable fraudulent financial reporting. The results of the analysis indicate that there is a significant relationship between factors such as stimulus, Opportunity and rationalization with fraudulent financial reporting in mining sector on the IDX. Meanwhile, Opportunity has no significant effect on Fraudulent Financial Reporting. Thus, there is an indication that the company has carried out effective supervision so that it is not able to influence the opportunities for fraud to occur.